ChemInform Abstract: Microwave‐Assisted Methylation of Dihydroxybenzene Derivatives with Dimethyl Carbonate. Issue 45 (October 2016) - Lui, Matthew Y.; Lokare, Kapil S.; Hemming, Ellen; Stanley, Jessica N. G.; Perosa, Alvise; Selva, Maurizio; Masters, Anthony F.; Maschmeyer, Thomas
Abstract: 1, 2‐ and 1, 4‐dihydroxybenzene undergo microwave assisted O‐methylation to give bis‐methyl ethers in excellent yields.